EFFECTIVENESS OF MOLECULAR-GENETIC DIAGNOSTICS DURING PERTUSSIS INFECTION FOCI EXAMINATION - A. S. Pimenova (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
Purpose: whooping cough diagnostics by molecular-genetic methods.Materials and methods. Under observation there were 4930 people during the period from 2012 to 2015. All samples were received in 8 schools of Moscow and the Moscow region: in 3 schools had been found children with whooping cough, in other 5 schools – only children with prolonged cough. Whooping cough diagnosis had been given earlier by bacteriological and serological methods. 430 clinical samples were studied by 2 methods: PCR with fluorescent hybridized detection of amplified products and isothermal amplification.Results. In three of eight schools whooping cough cases at 7 children at the age of 7, 9, 11 and 15 years were revealed earlier. The diagnosis of whooping cough at them was confirmed by means of bacteriological and serological methods. 33 positive DNA samples (7.7%) are revealed. DNA-positive samples are allocated from 18 pupils and 15 employees of schools. In two schools where earlier infection sources were established, 15 DNA-positive samples from which in three cases clinical manifestations were observed are revealed. In those schools where it wasn’t earlier established a source of an infection and examinations conducted it is long the coughing children, 18 DNA-positive samples are revealed, and in two cases clinical manifestations in the form of cough were observed.Conclusion. Performed research confirmed high efectiveness of molecular-genetic methods during pertussis infection foci examination in schools for infection source identification also amongst long coughing children.